Situs Sendang Duwur di Kabupaten Lamongan Jawa Timur - Izza Ainun Nurkholishoh; Wiwin Hartanto; Rully Putri Nirmala Puji (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
Abstract Sunan Sendang Duwur was one of the mayors whose role was equated with Walisongo in broadcasting Islam in Java. Sunan Sendang preaches culturally by acculturating the culture that has tradition in Sendang Duwur Village and internalizing it with Islamic values. His teachings about "mlakuho in the right, ilingo wong kang sak burimu" (walk on the right path, and remember the person who is behind you) until now is still relevant which is acculturated with the local culture is a tradition of selametan and sedekahan filled with tahlil recitation and bancaan. In addition, the Sendang Duwur Mosque whose vulnavular architecture is Joglo and acculturated with Javanese Hindu culture is also a trace of Sunan Sendang Duwur's cultural propaganda. This study discusses the toponymy and geographical location of Sendang Duwur, the history of restoration, architectural review, decoration and decoration and the significance of the Sendang Duwur site for Islamization in Java. The method in this study is a qualitative method with a historical approach by looking at and studying all aspects of the character's life. With this perspective, it is hoped that the topography and geographical location, history of restoration, architectural review, decoration and decoration and the significance of the Sendang Duwur site for Islamization in Java will be revealed.